Evaluation the Risk Factors that are Associated with Osteoporosis in Post Kidney Transplantation in a Sample of Iraqi Patients - Hasan, Angham A.; Abd alrazak, Munaf H.; M. Abbas Al-Temimi, Hassan (Iraqi Journal of Pharmaceutical Sciences, 2020)
Renal transplantation is a principal treatment option for end-stage kidney failure. Bone loss and fracture are serious complication of kidney transplantation, associated with morbidity and mortality. The pathogenesis of post transplantation bone loss is multifactorial and complex